Assessing the dyslipidemias: to fast or not to fast?. Issue 2 (19th April 2021) - Farukhi, Zareen; Mora, Samia
Abstract : Purpose of review: Nonfasting lipid testing has been introduced into several guidelines over the past decade or so however, the uptake into clinical practice has not been universal. This review highlights some of the prevalent reasons for provider reluctance to use nonfasting testing and the evidence to support nonfasting testing for routine screening in most patients. Recent findings: Several studies have found nonfasting lipids to be as, or more, strongly associated with cardiovascular disease (CVD) risk prediction. In particular, nonfasting tests improve system efficiency, are safe for patients with diabetes, the elderly, children, and in the vast majority of patients, do not need to be followed up with fasting studies due to severe hypertriglyceridemia. Summary: Nonfasting lipids are a convenient first test for screening that offers equivalent, if not improved CVD risk prediction. Common misconceptions about nonfasting tests are not supported by the evidence.